2021
DOI: 10.1186/s12935-021-02020-9
|View full text |Cite
|
Sign up to set email alerts
|

Myc-associated zinc-finger protein promotes clear cell renal cell carcinoma progression through transcriptional activation of the MAP2K2-dependent ERK pathway

Abstract: Background The dysfunction of myc-related zinc finger protein (MAZ) has been proven to contribute to tumorigenesis and development of multiple cancer types. However, the biological roles and clinical significance of MAZ in clear cell renal carcinoma (ccRCC) remain unclear. Methods MAZ expression was examined in ccRCC and normal kidney tissue by quantitative real-time PCR and Western blot. Statistical analysis was used to evaluate the clinical corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…All BC patients underwent curative radical cystectomy in urology department. The research protocol and sample collection were approved by the Ethics Committee of the Second Hospital of Hebei Medical University, and each patient signed a written informed consent [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All BC patients underwent curative radical cystectomy in urology department. The research protocol and sample collection were approved by the Ethics Committee of the Second Hospital of Hebei Medical University, and each patient signed a written informed consent [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Sanger sequencing was used to confirm the sequence. BC cell lines were seeded into a 24-well plate, and SF3A3-prom vector, oeKDM5C, or shE2F6 and the corresponding control vector were co-transfected to cells for 24 h. Luciferase activity was measured by Dual-Glo Luciferase Assay System (Promega, Madison, WI, USA) with Flash and Glow (LB955, Berthold Technologies) [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Research by Ren LX et al 64 . showed that MAZ was highly expressed in clear cell renal carcinoma (ccRCC) tissues, and upregulation of MAZ promoted the proliferation of ccRCC cells in vitro.…”
Section: The Relationship Between Maz and Malignant Tumorsmentioning
confidence: 99%
“…Immunofluorescence staining was performed as described previously. 19,21 Briefly, paraffin tissue sections were deparaffinized with xylene and rehydrated with gradient ethanol. The sections were immersed in PBS containing 0.5% Triton X-100 for 20 min and then washed thrice with PBS for 5 min each time.…”
Section: Immunofluorescence Stainingmentioning
confidence: 99%
“…Paraffin-embedded sections (4-μm thick) of clinical tissues were deparaffinized and subjected to in situ hybridization, as described previously. 19,21 According to the miRCURY LNATM microRNA ISH optimization kit manual (Exiqon, Vedbaek, Denmark), hybridization was performed with a fluorescent-labeled circAR-3 probe in hybridization buffer at 55°C for 1 h. The samples were washed in SSC buffer and sealed using DAPI Fluoromount-G. The images were captured using confocal microscopy (DM6000 CFS, Leica) and processed with LAS AF software.…”
Section: Fluorescence In Situ Hybridizationmentioning
confidence: 99%